Chaotic Circuits Applied to Secure Communications - García, Miguel; Sánchez-Azqueta, Carlos; Celma, Santiago (Jornada de Jóvenes Investigadores del I3A, 2023)
In this paper, we discuss the use of chaotic signals in cryptography. A comparative analysis of three different analogue chaotic communication systems is presented. The paper concludes with a discussion of some possible measures that could improve the security of these systems.